Students today, between Facebook, Google and Metacognition. Ideas to innovate in Higher Education - R. Elisondo; M. L. de la Barrera; D. Y. Rigo; D. I. Kowszyk; E. Fagotti Kucharski; A. Ricetti; M.R. Siracusa (Universitat Politècnica de València, 2016)
In college, as in other educational contexts, not enough to acquire a body of knowledge, it is essential to think about the cognitive processes to make independent and informed decisions regarding learning. Learning goes beyond cognitive issues, emotions and the posssibilities of think over of learning are critical in the complex processes of knowledge construction. The purpose of the study is to analyze metacognitive aspects related to academic learning on first year students of Kindergarten Teacher at the Universidad Nacional de Río Cuarto and Intituto Superior María Inmaculada (Argentina). At the first part of the research, students answered a general questionnaire on practices and habits of study and an inventory of learning patterns: ILS (Vermunt, 1998). Then, we conducted group interviews with students in order to acknowledge different views regarding the study practices, learning and teaching in contexts of higher education. The results show that most of students require external regulations to develop learning processes. We observe some difficulties in self-regulation of reading processes, writing and study in general. It is proposed to develop innovative strategies to promote thoughtful and metacognitive practices in students concerning learning in academic contexts.